Efficient aminoacylation of tRNA(Lys,3) by human lysyl-tRNA synthetase is dependent on covalent continuity between the acceptor stem and the anticodon domain. - Stello, T (1999)
In this work, we probe the role of the anticodon in tRNA recognition by human lysyl-tRNA synthetase (hLysRS). Large decreases in aminoacylation efficiency are observed upon mutagenesis of anticodon positions U35 and U36 of human tRNA(Lys,3). A minihelix derived from the acceptor-TPsiC stem-loop domain of human tRNA(Lys,3)was not specifically aminoacylated by the human enzyme. The presence of an anticodon-derived stem-loop failed to stimulate aminoacylation of the minihelix. Thus, covalent continuity between the acceptor stem and anticodon domains appears to be an important requirement for efficient charging by hLysRS. To further examine the mechanism of communication between the critical anticodon recognition elements and the catalytic site, a two piece semi-synthetic tRNA(Lys, 3)construct was used. The wild-type semi-synthetic tRNA contained a break in the phosphodiester backbone in the D loop and was an efficient substrate for hLysRS. In contrast, a truncated variant that lacked nucleotides 8-17 in the D stem-loop displayedseverely reduced catalytic efficiency. The elimination of key tRNA tertiary structural elements has little effect on anticodon-dependent substrate binding but severely impacts formation of the proper transition state for catalysis. Taken together, our studies provide new insights into human tRNA structural requirements for effective transmission of the anticodon recognition signal to the distal acceptor stem domain.